Papel do estresse oxidativo no desenvolvimento da fibrose pulmonar: efeitos do tratamento com vitamina c e/ou fotobiomodulação - Silva, Márcia Rodrigues da (2018)
Pulmonary fibrosis (PF) is a chronic and progressive lung disease characterized by progressive lesion of the lung parenchyma, inflammatory infiltrate and interstitial fibrosis. It is triggered by excessive and disordered deposition of collagen and other extracellular matrix components, resulting in severe changes in the architecture of the alveolus wall. Several factors can trigger PF including the exposure to chemical agents such as paraquat (PQ). Considering the absence of an effective treatment for FP, the objective of the present study was to investigate the effect of treatment with vitamin C and/or photobiomodulation (LED) on the course of PF. For this, C57BL6 mice were submitted to the induction of PF by the administration of PQ (10mg/kg, ip) and after 7 days of the induction, the mice were treated with Vitamin C (150mg/kg, ip) and/or irradiated with with LED (660 nm, 1x/day, for 5 consecutive days, 150s). Our data showed that both, LED and Vit C treatments isolated reduced the number of cells recruited into the lungs, and VitC+LED association did not produce any additional effect. Regarding the inflammatory mediators, our data showed that VitC treatment was more efficient than LED treatment. Our data showed elevated levels of SOD and catalase after treatment with vitamin C, while it was not able to revert the high tracheal contractile response. In conclusion, our results showed that oxidative stress can be a mechanism of inflammation and deposition of collagen in the lungs after the pulmonary fibrosis induced by PQ; and vitamin C appears to be an important tool for the treatment of this intoxication. It is noteworthy that vitamin C is inexpensive and may be a viable agent to be employed as therapy. Still, the association of Vit C with the LED is not showing additional effects that would justify its use.